Analytical Solution for Sound Radiation of Vibrating Circular Plates coupled with Piezo-electric Layers - K. Khorshidi; M. Pagoli (Mechanics of Advanced Composite Structures)
In the present study, the classical plate theory (CPT) was used to study sound radiation of forced vibrating thin circular plates coupled with piezoelectric layers using simply supported and clamped boundary conditions. The novelty of the study consists of an exact closed-form solution that was developed without any use of approximation. Piezoelectric, electrical potential loaded in the transverse direction satisfied the electric boundary conditions (open circuit) and Maxwell's electricity equation. It was assumed that no fluid loading occurred on the plate structure. The sound pressure and the sound power of the radiator were analytically obtained in a far field by using the Rayleigh integral. The proposed analytical method was validated using available data from the literature. Additionally, a few 2-D plots of the directivity pattern were illustrated for thin circular plates coupled with piezoelectric layers. Finally, the effect of boundary conditions, piezoelectric thickness, and the piezoelectric layer on the acoustical parameters were examined and discussed in details.